Phonetic Analysis of An-Nabr in the Arabic Short Film Al-Samāʾu Tumṭir: A Prosodic Study: Analisis Fonetik An-Nabr dalam Film Pendek Bahasa Arab ‘Al-Samāʾu Tumṭir: Kajian Prosodik - Muhammad Fadhil Husein; Muhammad Jafar Shodiq (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2025)
Purpose – This study aims to identify the position and realization of An-Nabr (stress) in the Arabic short film Al-Samāʾu Tumṭir, uploaded on the Arab Podcast channel. In addition, the study emphasizes the relevance of An-Nabr in contemporary phonetic research and expands the scope of Arabic prosody studies from a pedagogical level to an acoustic phonetic analysis using film as a medium. Design/methods/approach – The research employs a descriptive qualitative approach supported by acoustic phonetic analysis. The primary data consist of film dialogues, which were transcribed and annotated to identify stress. Validation was conducted through Praat software by measuring three universal stress parameters: duration (ms), intensity (dB), and fundamental frequency/F0 (Hz). Data validity was reinforced through inter-rater reliability and triangulation between manual annotation and acoustic analysis. Findings – The study identified 34 instances of An-Nabr, classified into three categories: (1) stress occurring according to the speaker’s intention to emphasize a particular meaning, (2) stress in sentences containing ḥarf nafi, ḥarf nahy, adawāt al-istifhām, and ḥarf syarṭ, and (3) stress following Arabic prosodic rules, particularly in sentences with fiʿil amr. The findings also demonstrate that An-Nabr is not only phonetic but also pragmatic. Stress can be categorized into lexical stress, phrasal stress, and emphatic stress, depending on the context of the utterance. Research implications/limitations – This study carries both theoretical and practical implications. Theoretically, it broadens Arabic prosody research by utilizing film as a natural prosodic corpus that represents speech more authentically than laboratory recordings. Practically, the findings can be applied to the development of phonetics and maharah kalām teaching materials, particularly in training learners’ prosodic awareness in Arabic. Teachers may employ films as a medium to practice stress in interrogative words, negation, and imperative sentences. Originality/value – This study is unique in that it: (1) employs an online short film as a data source for Arabic prosody, (2) applies acoustic analysis based on universal stress parameters, (3) offers methodological contributions through the combination of manual annotation, inter-rater validation, and acoustic measurement, and (4) recommends further research in the form of comparative studies between native speakers and non-Arab learners, as well as the utilization of other media corpora. Abstrak Tujuan – Penelitian ini bertujuan mengidentifikasi posisi dan realisasi An-Nabr (tekanan) dalam film pendek bahasa Arab Al-Samāʾu Tumṭir yang diunggah kanal Arab Podcast. Selain itu, penelitian menegaskan relevansi An-Nabr dalam kajian fonetik kontemporer serta memperluas ruang lingkup penelitian prosodi Arab, dari tataran pedagogis menuju analisis fonetik akustik berbasis media film. Desain/metode/pendekatan – Penelitian menggunakan pendekatan kualitatif deskriptif dengan dukungan analisis fonetik akustik. Data utama berupa dialog film, ditranskripsikan lalu dianotasi untuk mengidentifikasi tekanan. Validasi dilakukan melalui perangkat lunak Praat dengan pengukuran tiga parameter universal stres: durasi (ms), intensitas (dB), dan frekuensi dasar/F0 (Hz). Keabsahan data diperkuat dengan reliabilitas antar-penilai inter-rater reliability serta triangulasi antara anotasi manual dan analisis akustik. Temuan – Hasil penelitian menemukan 34 posisi An-Nabr yang terbagi dalam tiga kategori: (1) nabr yang muncul sesuai kehendak penutur untuk menekankan maksud tertentu, (2) nabr pada kalimat dengan ḥarf nafi, ḥarf nahy, adawāt al-istifhām, dan ḥarf syarṭ, serta (3) nabr yang mengikuti kaidah prosodi Arab, terutama pada kalimat dengan fi‘il amr. Temuan juga menunjukkan bahwa An-Nabr tidak hanya fonetik, tetapi juga pragmatik. Tekanan dapat diklasifikasikan menjadi lexical stress, phrasal stress, dan emphatic stress sesuai konteks ujaran. Implikasi/Keterbatasan Penelitian – Penelitian ini memiliki implikasi teoretis dan praktis. Secara teoretis, memperluas kajian prosodi Arab dengan memanfaatkan film sebagai korpus prosodik alami yang merepresentasikan ujaran lebih natural dibanding rekaman laboratorium. Secara praktis, hasil dapat dimanfaatkan dalam pengembangan materi ajar fonetik dan maharah kalām, khususnya melatih kesadaran prosodi pembelajar bahasa Arab. Guru dapat menggunakan film sebagai media latihan tekanan pada kata tanya, kata negasi, maupun kalimat perintah. Keaslian/nilai – Penelitian ini unik karena: (1) memanfaatkan film pendek daring sebagai sumber data prosodi Arab, (2) menerapkan analisis akustik berbasis parameter universal stres, (3) menawarkan kontribusi metodologis dengan kombinasi anotasi manual, validasi inter-rater, dan pengukuran akustik, serta (4) merekomendasikan penelitian lanjutan berupa kajian komparatif antara penutur asli dan pembelajar non-Arab maupun pemanfaatan korpus media lain.